2020
DOI: 10.24815/siele.v7i2.16663
|View full text |Cite
|
Sign up to set email alerts
|

Arising reading patterns in understanding literary texts

Abstract: This paper reviews reading attempts made by students at the lower secondary -- level in oral reading and retelling to understand literary texts. The study involved a qualitative research method in collecting data, which relates to the students’ reading patterns in understanding literary texts and the impact of students’ reading patterns on literary texts comprehension. The sample in this study comprised six average ability Form One (i.e. seventh grade) students from a secondary school. Data collection techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Teacher educators must also be very good at making a high-quality decision which does not only depend on facts or research but also their own experience and reliable resources (Singh & Samad, 2013). In ensuring to prepare teacher educators with this quality, the teacher training centres and university education faculties need appropriate education curriculum, policies for the pre-service teachers (Fathurohman & Cahyaningsih, 2021;Gopal & Singh, 2020), and self-efficacy beliefs to regulate and enhance their level of effective teaching (Saidi, 2020). These findings concur with those obtained by Prasangani (2019) who reported that in order for teachers to make students feel comfortable in learning, the teachers must find strategies to create a good rapport, exhibit good communication skills, create a conducive and pleasant learning environment, generate questions to initiate discussions with the students, exhibit good values and attitudes, make learning more meaningful and enjoyable, and provide positive feedback to the students during evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teacher educators must also be very good at making a high-quality decision which does not only depend on facts or research but also their own experience and reliable resources (Singh & Samad, 2013). In ensuring to prepare teacher educators with this quality, the teacher training centres and university education faculties need appropriate education curriculum, policies for the pre-service teachers (Fathurohman & Cahyaningsih, 2021;Gopal & Singh, 2020), and self-efficacy beliefs to regulate and enhance their level of effective teaching (Saidi, 2020). These findings concur with those obtained by Prasangani (2019) who reported that in order for teachers to make students feel comfortable in learning, the teachers must find strategies to create a good rapport, exhibit good communication skills, create a conducive and pleasant learning environment, generate questions to initiate discussions with the students, exhibit good values and attitudes, make learning more meaningful and enjoyable, and provide positive feedback to the students during evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Those images usually revolved around the basic qualities and values. It is the teacher's role to promote student cognitive development (Gopal & Singh, 2020;Yunus et al, 2021). This is also viewed as one of the prime purposes of education and teaching.…”
Section: Qualities Of An Ideal Teachermentioning
confidence: 99%
“…Shih and Huang (2018) point out that reading strategies have profiled and categorized the bottom-up (scanning and the use of cues setting) and top-down (skimming and driving schemata), meta-cognitive (covering apprehension and evaluating strategy use), affective (discussing reading with peer and collaborate with a peer in the reading tasks), and test-taking (language use and test-usefulness). The strategies aim at putting a remarkable correlation between reading proficiency and successful learning processes, in which students potentially tend to show a better improvement in tough reading performance (Chen et al, 2020) since oral reading forms multiply connect the readers' ideas to comprehend the literary texts (Gopal & Singh, 2020). Hence, a central goal of reading aims at assisting low-level students to become high-level proficiency readers through orders and intensities (Al-Qahtani, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Phonics, in a narrow sense, is defined as the letter-sound relationship in the English language (Bear et al, 2020). Broadly, it is regarded as an early English language reading method that fosters language learners" ability to identify and manipulate the phonemes used in oral language so they can learn how phonemes and graphemes correspond (Gopal & Singh, 2020;Papp, 2020). Phonics instruction, as a teaching activity, aims to teach language learners about the phoneme-grapheme correspondence (Gopal & Singh, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Broadly, it is regarded as an early English language reading method that fosters language learners" ability to identify and manipulate the phonemes used in oral language so they can learn how phonemes and graphemes correspond (Gopal & Singh, 2020;Papp, 2020). Phonics instruction, as a teaching activity, aims to teach language learners about the phoneme-grapheme correspondence (Gopal & Singh, 2020). It benefits all language learners, including EFL learners who are also struggling readers in English, in terms of decoding, reading accuracy, reading fluency, reading comprehension and spelling (International Literacy Association [ILA], 2019; Papp, 2020).…”
Section: Introductionmentioning
confidence: 99%